Pemanfaatan Website Aljazeera Learning Arabic sebagai Media Pembelajaran Mahārah Istimā’ - Masyithoh, Siti; Alwi, Itsnaini Muslimati (STIQ Amuntai, 2025)
Arabic language learning plays an important role as an international language used by millions of people in various countries. One of the obstacles faced by beginner learners is limited access to interactive learning media, especially in developing listening skills. The gap for beginner learners, experienced by class VIII B MTs Muhammadiyah 03 Ketro, is the limited learning media. Therefore, we employ conventional media for Arabic language learning. We chose Class VIII B because the students' Arabic language comprehension skills remain at a basic level.he digital era, the use of technology is one solution to overcome various learning challenges, including increasing student interest and understanding. The purpose of this study was to introduce and determine students' responses to the Al Jazeera Learning Arabic website as a learning medium. The method used in this study is qualitative with a descriptive approach. This method was chosen because it allows researchers to obtain data that is narrated in the form of words and sentences that are certainly related to the research being conducted. The Aljazeera Learning Arabic website has three features for beginner users, namely introduction, beginners, and basics, which are also equipped with evaluations. Some feedback from students, after studying together using the Al Jazeera Learning Arabic website, shows that the use of the website is very helpful in learning mahārah istima'. In addition, students feel helped by the website's existence as a learning medium for listening skills.